Bernard Lazarus Emanuel Sigamoney: A Multi-Faceted School Teacher’s Biography (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
Bernard Lazarus Emanuel Sigamoney was born in 1888 as part of the indentured labour community. His parents ensured that he received an education and this helped him climb the social ladder in local communities in Durban and Transvaal. Consequently, his name became linked to the scout, sport, social, religious, and political movements of the day. He died in 1963 leaving behind a footprint that calls for recognition. This article placed Sigamoney, a South African politically active schoolteacher, under scholarly analysis. His circumstances of being subjected to institutional racism and forced removals make a coherent narrative an impossible task for a historian. Therefore, a disjointed but important narrative from the scraps left behind in newspaper accounts, internet searchers, and general history sources was constructed. These accounts revealed how he contributed to South African political liberation on a national and local community level. The political networks he created also present readers with a window into twentieth century resistance movements in local communities. His voice was also present in the early socialist and later anti-apartheid sports movements. He used his position as a schoolteacher to launch actions that challenged the segregation and apartheid regime of the day.